2004
DOI: 10.1128/jvi.78.10.5088-5096.2004
|View full text |Cite
|
Sign up to set email alerts
|

Differential Cell Killing by Lymphomagenic Murine Leukemia Viruses Occurs Independently of p53 Activation and Mitochondrial Damage

Abstract: Upon inoculation into AKR mice, mink cell focus-forming murine leukemia virus (MCF MLV) accelerates thymic lymphoma formation. During the preleukemic phase of disease, we observed the induction of apoptosis in thymic lymphocytes. A similar induction of apoptosis was observed for cultured mink epithelial cells after MCF13 MLV infection. In this study, the relevance of viral pathogenicity to cell killing was determined by testing the susceptibility of various cell types from different species to lymphomagenic ML… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
11
0

Year Published

2004
2004
2010
2010

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 48 publications
0
11
0
Order By: Relevance
“…We have observed a similar phenomenon for mink cell focus-forming murine leukemia virus (MCF13 MLV), which induces apoptosis in thymic lymphocytes of inoculated AKR mice during the preleukemic period (31). Upon testing of cultured cell lines, we observed that mink cells were similarly susceptible to MCF13 MLV-induced cell killing (18). It has been shown that cell killing by pathogenic retroviruses such as FeLV-FAIDS, ts-1 MoMLV, MuLV-NT40, and FrCas E MLV strongly correlates with the inefficient processing of the precursor Env glycoprotein, resulting in its intracellular accumulation in a cell type-specific manner (11,15,21,25).…”
mentioning
confidence: 69%
See 1 more Smart Citation
“…We have observed a similar phenomenon for mink cell focus-forming murine leukemia virus (MCF13 MLV), which induces apoptosis in thymic lymphocytes of inoculated AKR mice during the preleukemic period (31). Upon testing of cultured cell lines, we observed that mink cells were similarly susceptible to MCF13 MLV-induced cell killing (18). It has been shown that cell killing by pathogenic retroviruses such as FeLV-FAIDS, ts-1 MoMLV, MuLV-NT40, and FrCas E MLV strongly correlates with the inefficient processing of the precursor Env glycoprotein, resulting in its intracellular accumulation in a cell type-specific manner (11,15,21,25).…”
mentioning
confidence: 69%
“…We previously showed that mink epithelial cells were susceptible to MCF13 MLV-induced cell killing, whereas other types of cells, such as Mus dunni fibroblasts, were resistant (18). To determine whether there is a correlation between Env precursor accumulation and virus-induced cell killing, we compared intracellular levels of gPr80 env in mink epithelial cells and M. dunni fibroblasts after infection with MCF13 MLV at a multiplicity of infection (MOI) of 3.…”
mentioning
confidence: 99%
“…5,63 However, other experiments have shown that the accumulation of unintegrated viral DNA and the reduced formation of circles can be uncoupled from cell killing. 29,59,62 It should also be noted that high concentrations of unintegrated DNA would normally be associated with high frequency of integration, which may be toxic to cells. The effects of high DNA concentration and highfrequency integration on cell survival can be tested by manipulating experimental conditions, that is, by using a high m.o.i., or infection methods that increase the effective m.o.i.…”
Section: Cytopathic Effects Of Retroviral Infection and Possible Relementioning
confidence: 99%
“…Several lines of research, beginning with the early studies of Temin and colleagues, 60 have led to the idea that unintegrated viral DNA may induce cell killing. 58,59,62 It was recently suggested that high concentrations of unintegrated viral DNA, containing free ends, might be sensed as irreparable DNA damage in the cell, and that the NHEJ system may suppress an apoptotic response by joining such ends to form circles, which are a dead-end product. 5,63 However, other experiments have shown that the accumulation of unintegrated viral DNA and the reduced formation of circles can be uncoupled from cell killing.…”
Section: Cytopathic Effects Of Retroviral Infection and Possible Relementioning
confidence: 99%
See 1 more Smart Citation